Redefinition of the millipede subgenus Megaphyllum sensu stricto Verhoeff, 1894 and neotype designation for Megaphyllum austriacum (Latzel, 1884) (Myriapoda: Diplopoda: Julida: Julidae) - Lazányi, Eszter; Vagalinski, Boyan (Zootaxa, 2013)
Megaphyllum sensu stricto, i.e. the nominotypical subgenus of the very complicated genus Megaphyllum Verhoeff, 1894, is redefined on the basis of examination of type and non-type material and literature data. Four species-groups including twenty species in all are listed, and the identity of M. austriacum (C. L. Koch, 1838) is clarified with a proposal of neotype designation under ICZN Article 75.6. in order to stabilize the current usage of the name. Prevailing usage of M. silvaticum (Verhoeff, 1898) syn. nov. (nomen protectum) over the senior synonym M. nigrescens (Latzel, 1884) (nomen oblitum) is maintained under ICZN Article 23.9. M. banaticum (Verhoeff, 1899) is syn. nov. of M. erythronotum (Latzel, 1884) comb. nov., M. bosniense cotinophilum (Loksa, 1962) syn. nov. of M. bosniense bosniense (Verhoeff, 1897) and M. transsylvanicum transdanubicum (Loksa, 1962) syn. nov. of M. transsylvanicum transsylvanicum (Verhoeff, 1897). M. unilineatum (C. L. Koch, 1838) is new to the fauna of Turkey.